Deteksi Jarak Bola Pada Robot Kiper Sepak Bola Menggunakan Hough Circle Transformation Berbasis Raspberry Pi - Tunggal Manda Ary Triyono; Hurriyatul Fitriyah; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The goalkeeper robot is part of robosoccer team which is in charge of catching the ball correctly and also effectively. To make the movement of goalkeeper robot correct and also effective, the goalkeeper robot must be able to know how far the distance between the ball and itself. Therefore, ball distance detection system on the goalkeeper robot using Hough Circle Transformation based on Raspberry Pi was made. This research used webcam Logitech C525 and Raspberry Pi 3 Model B. The images captured by camera will be processed to obtain binary images with minimum noise. Then cartesian coordinates and diameter of the ball will be obtained by using Hough Circle Transformation. The distance between ball and goalkeeper robot is calculated using comparison between ball diameter that detected by system and diameter at the references distance. Ball coordinate in the frame can also be used to get position and angle direction of the ball. Based on the test, best angel of view of camera for distance and angle detection is 47,2o with the accuracy of distance detection is 97,69% and accuracy of angle detection is 94,69%. The average computation time is 158.54 ms.